Incidence of stuttering in twins and singletons in selected schools in Ibadan township (1990)
This study was carried out to survey the incidence of stuttering in two sets of population, the twins and singletons. The sample of the study came from selected schools in Ibadan township and the stutterers in their families. Using the chi-Square statistics. It was found out that the incidence of stuttering in twins is not significantly higher than that of singletons and that the incidence in males is not significanly diiferent from the incedence of females